2015
DOI: 10.1007/s11738-015-1875-y
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and zygotic embryos share common developmental features at the onset of plant embryogenesis

Abstract: In many vascular plants, zygotic reproduction regularly alternates with different types of asexual reproduction, so embryos can develop not only from fertilized egg cells, but also from induced somatic cells through the process of somatic embryogenesis. Although somatic and zygotic embryogenesis are not directly correlated, their common features are presented, demonstrating that the origin and development of the somatic embryo morphologically and physiologically resemble zygotic embryogenesis at certain points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 179 publications
2
23
0
Order By: Relevance
“…The formation of the embryo sac and subsequent double fertilization and the early development of the embryo and endosperm have recently been studied in Agave tequilana Weber var. This observed process was similar to what is described for the majority of angiosperms (Lau et al 2012;Leljak-Levanić et al 2015). This study was carried on clarified mature and immature ovules without cutting the tissues with a microtome in order to maintain the cells in their original site inside the embryo sac.…”
Section: Zygotic Embryogenesis In Agave Tequilanasupporting
confidence: 68%
“…The formation of the embryo sac and subsequent double fertilization and the early development of the embryo and endosperm have recently been studied in Agave tequilana Weber var. This observed process was similar to what is described for the majority of angiosperms (Lau et al 2012;Leljak-Levanić et al 2015). This study was carried on clarified mature and immature ovules without cutting the tissues with a microtome in order to maintain the cells in their original site inside the embryo sac.…”
Section: Zygotic Embryogenesis In Agave Tequilanasupporting
confidence: 68%
“…Finally, at nine DAP the zygote suffers a first asymmetric cell division giving rise to a two-celled proembryo consisting of cells with different developmental fates; the basal cell that will form the suspensor and the apical cell which is the first cell of the embryo proper and that through a series of coordinated cell divisions will form the embryo. This observed process was similar to what is described for the majority of angiosperms (Lau et al 2012;Leljak-Levanić et al 2015). Furthermore, the same pattern has been observed in another genus member of the Asparagaceae family (formerly Agavaceae): Polianthes tuberosa (González-Gutiérrez, to be published elsewhere).…”
Section: Zygotic Embryogenesis In Agave Tequilanasupporting
confidence: 85%
“…It has been found that many genes related to SE are involved in stress signaling pathways [80]. Totipotent cells can be formed by the dedifferentiation of somatic cells, which are induced by the addition of certain plant hormones, culture under different stress conditions or their simultaneous application [81]. For example, high temperatures increase auxin signaling [82] and significantly reduce the content of available water [83].…”
Section: Discussionmentioning
confidence: 99%